2015
DOI: 10.1002/chem.201502162
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Nature of Co‐components and Their Impact on Pd Structure: X‐ray Absorption Studies on Toluene Acetoxylation Catalysts

Abstract: Co-components are a powerful tool to tune the performance of catalysts, but their nature and their impact on the catalysts is often controversially discussed. In this study X-ray absorption spectroscopy (XAS) was employed to elucidate the nature of co-components and their impact on the catalytic reaction. In anatase-supported Pd-based catalysts for the gas-phase acetoxylation of toluene, less noble co-components (e.g., Mn, Co, and Sb) spread over the support in their oxidic form and changed their valence state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
(215 reference statements)
0
4
0
Order By: Relevance
“…After testing these two series of catalysts, one concluded that 10% Pd and 8% Sb on TiO 2 (anatase) was the right combination and hence this was used as a model catalyst in the next runs. Besides Sb, the influence of various other co-components (e.g., Au, Mn, Co) was also investigated and characterized by X-ray absorption spectroscopy (XAS) in order to elucidate the nature of co-components and their impact on the catalytic activity/selectivity [81]. It was observed that Mn and Co oxides spread on the support TiO 2 surface while Au forms separate small metal (Au) nanoparticles besides Pd particles and exhibits a different influence on the catalytic performance.…”
Section: Methodsmentioning
confidence: 99%
“…After testing these two series of catalysts, one concluded that 10% Pd and 8% Sb on TiO 2 (anatase) was the right combination and hence this was used as a model catalyst in the next runs. Besides Sb, the influence of various other co-components (e.g., Au, Mn, Co) was also investigated and characterized by X-ray absorption spectroscopy (XAS) in order to elucidate the nature of co-components and their impact on the catalytic activity/selectivity [81]. It was observed that Mn and Co oxides spread on the support TiO 2 surface while Au forms separate small metal (Au) nanoparticles besides Pd particles and exhibits a different influence on the catalytic performance.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, Sb incorporation promotes growth of Pd par-ticles. 15 The atomic ratio of Pd to Sb in these particles is around 5. Unfortunately, this catalyst was found to undergo deactivation during the course of reaction after several hours of operation.…”
Section: Introductionmentioning
confidence: 99%
“…The XANES can be used to identify the chemical species from oxidation states of the absorbing atoms. Synchrotron XANES has been employed for structural investigation of a variety of nanoparticles including iron oxides [11], zinc ferrite [12] and toluene acetoxylation catalysts [13]. The only report involving MnBi was to study the effect of Cu doping [14].…”
Section: Introductionmentioning
confidence: 99%